PEMBUNGAAN TANAMAN SPATIFILUM (Spathiphyllum wallisii Regel) AKIBAT PENGARUH RESIDU PEMBERIAN BENZILADENIN (BA) PADA PERIODE KEDUA - Rugayah, Rugayah; Warganegara, Hayane Adeline; Karyanto, Agus; Ardanti, Ade Novia (Universitas Lampung, 2025)
Spatifilum is classified as a shade plant that can survive in environments with minimal sunlight or shading Spatifilum plants are known to absorb toxins or clean indoor air from pollutants such as benzene and formaldehyde. Efforts to stimulate flowering and the emergence of spatifilum seedlings include using a growth regulator in the form of benzyladenine (BA). The aim of this research was to determine the difference in the effect of residual BA with and without BA on the flowering of spatifilum plants in the second period. Data collection was carried out in August – November 2022 at the Horticulture Greenhouse, Faculty of Agriculture, University of Lampung. This research used a Complete Randomized Block Design (RAKL) with a single treatment. The treatment consisted of 5 BA concentration treatments, namely 0 ppm, 20 ppm two applications, 20 ppm four applications, 40 ppm two applications, and 40 ppm four applications with four repetitions. The data from this research were analyzed using the barlet test and the additivity test was carried out using the Tukey test. Then the data was analyzed using variance (Anara) and orthogonal contrast tests. The results of the research showed that there were significant differences in the variables of increasing the number of seedlings and increasing the number of flowers. BA concentration of 20 ppm was significantly able to increase the number of offspring compared to a concentration of 40 ppm, meanwhile, a concentration of 40 ppm with a frequency of giving 2x significantly increased the number of flowers compared to a frequency of giving 4x